З документів фонду 1633 ЦДІАК до історії Глухівщини ХVІІІ ст. - Мицик, Ю.А.; Тарасенко, І.Ю. (Сіверщина в історії України, 2020)
У статті розглядаються матеріали фонду 1633 Центрального державного історичного архіву України, м. Київ (ЦДІАК України). Тут зберігаються документи домової економічної канцелярії гетьмана Кирила Розумовського, малодослідженої установи
Гетьманщини. Вони стосуються в основному міст і сіл сучасної
Сумщини і тому мають особливе значення для краєзнавців. Чимало матеріалів стосуються економічного життя краю – торгівлі,
промислів, оренди тощо, розкривають певні аспекти соціальної
історії, судових установ, демографії. У зв’язку з великим обсягом
справ фонду аналізуються лише ті документи, які мають безпосереднє відношення до м. Глухова та с. Сопич. The article deals with the materials of the Fund 1633 of the Central
State Historical Archives of Ukraine, Kyiv (CDIAC of Ukraine). There are 95
cases in total. The documents cover a narrow chronological period: 1751–
1764. Here are stored the documents of the economic office of Hetman
Kyrylo Rozumovskyi, a small-scale institution of the Hetmanate. They
refer mainly to the cities and villages of the modern Sumy region and are
therefore of particular importance to local lore. Many materials relate to the
economic life of the region - trade, crafts, leases, etc., reveal certain aspects
of social history, judicial institutions, demographics. Although these cases
mention Hlukhiv, but it is still about the property of Rozumovskyi (villages
Sopych, Kucherivka, Marchyshina Budda, Potapivka, Seredyno Budda),
which are localized on the territory of the modern Sumy region, mainly
in the Hlukhiv district. Due to the large volume of cases of the Fund, only
those documents that are directly related to Hlikhivv and Sopych villages
are analyzed. The Fund has a number of cases of establishing the origin
of Ukrainian and Russian peasants, documents on the investigations of
the misappropriation of various possessions and soils, orders, certificates,
information, reports submitted to the economic office.